Virtual reality-based cloud BIM platform for integrated AEC projects - Goulding, J.; Rahimian, F.; Wang, Xiangyu (Department of Computer Science, 2014)
Building Information Modelling (BIM) has demonstrated the need for integrating collaborative design teams' "project data", to not only help coordinate the design, engineering, fabrication, construction, and maintenance of various trades, but also facilitate project integration and interchange. Numerous potential benefits have inspired several countries to consider the implications of implementing BIM Level 3 (Cloud) as an innovative way of further enhancing the design, management and delivery process, ergo - a paradigm shift towards Integrated Project Delivery (IPD). Amongst the myriad of the available innovative approaches, web-based platforms are particularly beneficial for integrating visualisation components to give continuous sharing of relevant information for geographically dispersed end users. This study presents a game environment supported by a web-based Virtual Reality cloud platform for integrated AEC projects. This paper further explains the adapted Unified-Software-Development-Process of specifying this cloud computing platform, which employed iterative phases of Elaboration, Construction and Transition. This study presents new understanding and insight into the causal drivers and influences associated with successful decision-making design in non-collocated design teams. Research findings form a stepping-stone for developing new relationship models in collaborative environments, particularly gaming interfaces.